The study of biological characteristics and pests of raspberry’s remontant kwanza and tulano varieties in the unheated greenhouse - Gabrielyan, G. S.; Petrosyan, A. A.; Baghdasaryan, T. A.; Hakobyan, A. E.; Asatryan, S. S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The studies of the features of raspberry’s varieties and the species composition of pests in the conditions of the unheated hydroponic greenhouse covered with a synthetic membrane operating in the Artik community of Shirak region, led to the conclusion, that the Kwanza variety provides a high commodity yield with high fruit quality. The yield also stood out for its storage capacity, transportability, as well as with relatively average resistance to pests and diseases. However, it must be noted, that 3 types of pests and 2 types of diseases were found on the plants of both varieties of raspberry. Շիրակի մարզի Արթիկ համայնքում գործող սինթետիկ թաղանթով ծածկված չտաքացվող հիդրոպոնիկ ջերմատան պայմաններում մորենու սորտերի առանձնահատկությունների ու վնասակար օրգանիզմների տեսակային կազմի ուսումնասիրություններից հանգել են հետևյալ եզրակացությունների, որ բարձր ապրանքային բերք և պտղի որակ ապահովել է Կվանզա սորտը, որն աչքի է ընկել նաև պտուղների պահունակությամբ, փոխադրունակությամբ, ինչպես նաև վնասատուների և հիվանդությունների դեմ համեմատաբար միջին դիմացկունությամբ: Այնուամենայնիվ մորենու երկու սորտերի վրա հայտնաբերվել են վնասատուների 3 և հիվանդությունների 2 տեսակներ։ В условиях неотапливаемой гидропонной теплицы, покрытой синтетической пленкой, функционирующей в общине Артик Ширакского марза, исследования особенностей ремонтантных сортов малины Kwanza, Tulano и видового состава вредных организмов позволили сделать следующие выводы: сорт Kwanza обеспечил высокую урожайность и качество плодов, которые также отличались способностью хранить плоды, транспортабельность, а также относительно средней устойчивостью к вредителям и болезням. Однако на обоих ремонтантных сортах малины Kwanza, Tulano обнаружено 3 вида вредителей и 2 вида болезней.
Keywords: Biotechnology; Greenhouse